2022
DOI: 10.3390/antiox11071414
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside Ameliorates Radiation Damage by Reducing Mitochondrial Oxidative Stress in the Submandibular Gland

Abstract: Radiotherapy for patients with head and neck cancer inevitably causes radiation damage to salivary glands (SGs). Overproduction of reactive oxygen species (ROS) leads to mitochondrial damage and is critical in the pathophysiology of SG radiation damage. However, mitochondrial-targeted treatment is unavailable. Herein, both in vitro and in vivo models of radiation-damaged rat submandibular glands (SMGs) were used to investigate the potential role of salidroside in protecting irradiated SGs. Cell morphology was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, intracellular antioxidative mechanisms were also detected to assess the protective effects (riluzole, EGCG, and Ri@EGCG-2 NPs, 40 μg/mL). 48 Consistent with Collectively, these results demonstrated the great intracellular protective effects against oxidative stress.…”
Section: Ri@egcg Nps Fabrication and Characterizationsupporting
confidence: 79%
See 1 more Smart Citation
“…Furthermore, intracellular antioxidative mechanisms were also detected to assess the protective effects (riluzole, EGCG, and Ri@EGCG-2 NPs, 40 μg/mL). 48 Consistent with Collectively, these results demonstrated the great intracellular protective effects against oxidative stress.…”
Section: Ri@egcg Nps Fabrication and Characterizationsupporting
confidence: 79%
“…In addition, a 2′,7′-dichlorofluorescein diacetate (DCFH-DA) fluorescent probe was utilized to detect ROS levels of HT 22 cells treated by H 2 O 2 (400 μM), and the results showed that both Ri@EGCG-2 NPs and EGCG significantly decreased the ROS levels compared with only the H 2 O 2 stimulation group (PC) and riluzole group (Figure E,F). Furthermore, intracellular antioxidative mechanisms were also detected to assess the protective effects (riluzole, EGCG, and Ri@EGCG-2 NPs, 40 μg/mL) . Consistent with the results of DCFH-DA assays, Ri@EGCG-2 NPs and EGCG significantly upregulated the levels of glutathione (GSH)/glutathione disulfide (GSSG) and superoxide dismutase (SOD) and downregulated the levels of malondialdehyde (MDA) compared with PC and riluzole groups (Figure G–I).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, the re-functionalization of red blood cell-based nanomaterials to enhance the targeted drug delivery strategy at the site of oxidative stress injury can also be considered as a key reference [ 125 ]. In addition, salidroside has been identified as a mitochondria-targeted antioxidant to prevent salivary gland damage caused by X-ray radiation [ 126 ]. The development of drugs that target 131 I-damaged organs and tissues may provide an alternative solution to the side effects associated with high doses of traditional antioxidants.…”
Section: Challenges and Prospectsmentioning
confidence: 99%